Et forsvar for populærkulturen – En præcisering af det populærkulturelle begreb og en kritisk læsning af Adornos syn på populærkulturen - Hegnsvad, Kristoffer (Slagmark - Tidsskrift for idéhistorie, 2018)
This article explores the concept of popular culture and popular art. When Michael Moore’s Fahrenheit 9/11 received the Golden Palm in Cannes in 2004, the French press and director Jean-Luc Godard joined in a critique of the jury’s choice. The press discussed the possibility of the festival loosing its status as the most prestigious festival of art cinema after giving the prize to an American political documentary. Godard criticized Michael Moore for being to direct and not communicating through more subtle aesthetics. Between the lines of both critiques one find a devaluation of popular art often seen in modern aesthetic theory and this article tries to refute this devaluation in a critical reading of Theodor W. Adorno’s view on the popular.